Challenges and Advances in Diagnosis and Treatment of Leptomeningeal Disease (LMD) - Ferguson, Sherise D.; Fomchenko, Elena I.; Guerrieri, Renato A.; Glitza Oliva, Isabella C. (Frontiers in Oncology, 2022)
Leptomeningeal disease (LMD) is a devastating category of CNS metastasis with a very poor prognosis and limited treatment options. With maximal aggressive therapy, survival times remain short and, without treatment, prognosis is measured in weeks. Both LMD diagnosis and treatment are challenging topics within neuro-oncology. In this review, we discuss the advances in LMD diagnosis with a focus on the role of circulating tumor DNA (ctDNA) and discuss the role of targeted and immunotherapy in LMD treatment.